Domino Card Media Development to Improve Critical Thinking Skills of 5th Grade Elementary School Students - Wilda Lailatul Fitri; Fitri Hilmiyati; Juhji Juhji (Al-Qalam Institute, 2026)
The development of innovative learning media is essential to enhance students’ critical thinking skills in elementary education. This study aims to develop Domino Card learning media for fifth-grade students to improve their critical thinking skills. The research was motivated by preliminary observations at MI Mathla’ul Huda, which revealed that students’ critical thinking abilities were relatively low due to the limited use of instructional media supporting higher-order thinking. The study employed a Research and Development (R&D) approach using the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. Validation results showed that the media expert awarded a score of 86%, while the material expert gave 94%, indicating high validity. The effectiveness of the media was measured through pre-test and post-test assessments. The average pre-test score was 60.37, increasing to 86.29 in the post-test. The N-gain value was 0.64 (64%), categorized as “Quite Effective.” These findings indicate that the developed domino card media effectively enhances students’ critical thinking skills.